Efektivitas Kebijakan Larangan Berpacaran terhadap Perilaku Prososial Siswa Kelas IX SMP Negeri 5 Sipahutar dalam Kerangka Pendidikan Karakter Pancasila - Usni Caroline Hikaru Simanjuntak; Limunada Umbase (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2026)
To address the negative impacts of teenage romantic relationships on peer dynamics and academic achievement at SMP Negeri 5 Sipahutar, school authorities implemented a regulation prohibiting dating, in line with Pancasila character education principles. This study aimed to evaluate the influence of this policy on fostering positive social behavior among ninth-grade students. The research employed a quantitative descriptive approach and involved 81 students as respondents. Data were collected using a four-level multiple-choice agreement questionnaire consisting of ten items. The analysis results showed a total score of 2707, a mean score of 33.42, a standard deviation of 4.8, and an average scale score of 3.34. The findings revealed that 78.2% of students agreed that the regulation encouraged peer cooperation, improved discipline in obeying school rules, and supported effective group learning. In addition, the policy appeared to contribute to a more positive school environment by reducing distractions associated with adolescent dating behavior. These findings indicate that school-based regulations can play an important role in shaping adolescent character and social behavior based on national values. Therefore, such policies may serve as an effective preventive strategy for educational institutions that aim to strengthen character education and promote responsible student conduct.